The Impact of Psychological Stress on the Development of Internal Diseases (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Psychological stress represents a multidimensional physiological and behavioral response that, when chronic, disrupts homeostatic mechanisms and contributes to the onset of numerous internal diseases. The study synthesizes contemporary findings (2017–2025) on neuroendocrine, immune, and metabolic pathways linking stress to systemic disorders. Analysis of cohort studies, meta-analyses, and mechanistic reviews reveals that prolonged activation of the hypothalamic–pituitary–adrenal axis and the sympathetic nervous system induces hormonal imbalance, inflammation, immune dysregulation, and microbiota alterations. These changes increase the risk of cardiovascular, autoimmune, metabolic, respiratory, and oncological diseases. Notably, evidence from the CARDIA and CHIEF cohorts, as well as meta-analyses in Frontiers and Molecular Cancer, highlights chronic stress as an independent etiological factor of hypertension, diabetes, autoimmune disorders, and tumor progression. Behavioral mediators such as unhealthy diet, sedentary lifestyle, and substance abuse amplify these effects. The findings emphasize the necessity of integrating stress-management interventions—psychotherapy, mindfulness, and physical activity—into preventive medicine. Despite strong associative evidence, causal mechanisms remain insufficiently explored, underscoring the need for randomized interventional studies to clarify stress-disease pathways and therapeutic targets.